IN-SILICO STUDY OF BIOACTIVE COMPOUNDS OF NATURAL MATERIALS AS A JAK- SIGNAL TRANSDUCER AND ACTIVATOR OF TRANSCRIPTION INHIBITOR FOR ANTI-ALOPECIA - Mustarichie, Resmi; Megantara, Sandra; Saptarini, Nyi Mekar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study aims to examine the compounds contained in herbs for the treatment of anti-alopecia by in-silico computation. Methods: JAK (Janus Kinase) regulates the activation of key hair follicle populations such as the hair germ and improves the inductivity of cultured human dermal papilla cells by controlling a molecular signature enriched in intact, fully inductive dermal papillae. JAK2 which was a member of Janus family was used in this study as a receptor (PDB code: 4C61) and 15 compounds normally found in five herbals traditionally used as hair growth as ligands. Molecular modeling of bioactive compounds was performed using MarvinSketch and Prediction of physicochemical properties by ligand scout software. Molecular docking was performed using ligand scout, AutoDock Vina, and PyMOL. Binding affinity (Ei), inhibition constant (Ki), hydrogen bond interaction, and hydrophobic interaction were evaluated to find which of herbs potentially for anti-alopecia. Results: Among 15 compounds studied three of them, 6-hydroxy genistein, coreximine, and scoulerine interacted well with JAK2's active pocket so it can inhibit JAK- signal transducer and activator of transcription. 6-hydroxy genistein interacted with Asp994, Gly993 Met929, Val863, Leu983, Ala880, and Leu855 whereas coreximine and scoulerine interacted with Leu932, Pro933, Tyr931 and Pro933, Tyr931, Ala880, Val863, Leu983, Leu855, respectively. Conclusion: These results predicted that three compounds, namely, 6-hydroxy genistein, coreximine, and scoulerine which come from Dadap leaves (Erythrina variegata var. orientalis (L.) Merr.) were strongly had the link with JAK2 indicating that this plant extract may be used as hair growth agent/ anti-alopecia. As compounds studied was based on the literature survey, our results suggest compounds from six herbals studied should firstly be tested in-vivo for its anti-alopecia activity, fractionated, elucidated, to check as to whether their compounds responsible for anti-alopecia using the method developed in this paper.